English Result. Intermediate: Student's Book - Hancock M. Mark (Oxford, Oxford University Press, 2012)
Learn the language you need and put it into practice immediately with English Result. How to lessons provide a clear focus and practical language outcomes Two-page lessons use a whole page of visuals to motivate learners Lessons use curiosity, entertainment, personalization, and challenge to keep motivation high Practical speaking syllabus includes spoken production and spoken interaction I can tickline in every lesson encourages immediate self-assessment